The Persian Version of Menopause Rating Scale (MRS): A Psychometric Study - Allahverdipour H; Asghari Jafarabadi M; Burri A; Javadivala Z (Dove Medical Press, 2020)
Hamid Allahverdipour,1 Mohammad Asghari Jafarabadi,2,3 Andrea Burri,4 Zeinab Javadivala5 1Research Center of Psychiatry and Behavioral Sciences, Department of Health Education and Promotion, Tabriz University of Medical Sciences, Tabriz, Iran; 2Road Traffic Injury Research Center, Tabriz University of Medical Sciences, Tabriz, Iran; 3Department of Statistics and Epidemiology, Tabriz University of Medical Sciences, Tabriz, Iran; 4Institute for Sex Counselling and Sexual Sciences (ISCSS), Zurich, Switzerland; 5Department of Health Education and Promotion, Tabriz University of Medical Sciences, Tabriz, IranCorrespondence: Zeinab JavadivalaDepartment of Health Education and Promotion, Tabriz University of Medical Sciences, Tabriz 14711, Iran+98-411-3344731Email zjavadivala791@gmail.comObjective: Menopause-related symptoms can strongly affect health-related quality of life (HRQOL) in most peri-menopausal women. The aim of the present study was to explore the psychometric properties of a culturally adapted and translated Persian version of the Menopause Rating Scale (MRS).Study Design: The study was conducted on a random sample of 270 middle-aged women (age range 40– 60 yrs) selected from 25 urban health service centers across Tabriz, Iran. Content validity was evaluated by a panel of 11 experts. Construct validity was assessed by exploratory factor analyses with Varimax rotation and principal axis factoring extraction method and by confirmatory factor analyses. Internal consistency and test–retest reliability were assessed with Cronbach’s alpha and intra-class correlation coefficient (ICC), respectively. In addition, the feasibility of the measure was judged based on ceiling and floor effects.Results: Content validity of the measure was good with a mean content validity index (CVI) and mean content validity ratio (CVR) of 0.88 and 0.94, respectively. Exploratory factor analyses identified three factors accounting for 47.69% of the variance. Confirmatory factor analyses found the original three-factor model to have the best fit to the data. Cronbach’s alpha coefficient (0.85) and the test–retest reliability score (0.91) indicated good internal consistency.Conclusion: The Persian version of the MRS demonstrated excellent reliability and validity. It can therefore be used in both clinical and research settings to assess menopause-related symptoms and associated quality of life.Keywords: Menopause Rating Scale, psychometric, menopause, Persian